Patient-Reported Prevalence of Non-motor Symptoms Is Low in Adult Patients Suffering From 5q Spinal Muscular Atrophy - Günther, René; Wurster, Claudia Diana; Cordts, Isabell; Koch, Jan Christoph; Kamm, Christoph; Petzold, Daniel; Aust, Elisa; Deschauer, Marcus; Lingor, Paul; Ludolph, Albert Christian; Hermann, Andreas (Frontiers in Neurology, 2019)
Background: 5q spinal muscular atrophy (SMA) is an autosomal recessive lower motoneuron disease caused by deletion or mutations in the survival motor neuron 1 gene (SMN1) which results in reduced expression of full-length SMN protein. The main symptoms are caused by spinal motor neuron demise leading to muscle atrophy, and medical care mostly refers to motor symptoms. However, new insights of recent studies in severe SMA type I revealed disease involvement of several non-motor regions, for example cardiac, vascular, sensory nerve involvement and thalamic lesions. Non-motor symptoms (NMS) were previously described in many neurodegenerative diseases i.e. Parkinson’s disease and, importantly, also amyotrophic lateral sclerosis. Methods: We screened for NMS in 70 adult patients with SMA type II (SMAII) and type III (SMAIII) and 59 age/sex-matched healthy controls (controls) in a multicenter cross-sectional study including 5 different centers with specialized expertise in medical health care of motoneuron diseases. We used a self-rating questionnaire including 30 different items of gastrointestinal, autonomic, neuropsychiatric, and sleep complaints [NMS questionnaire (NMSQuest)], which is a validated tool in Parkinson’s disease. Results: Total NMS burden was low in adult SMA (median: 3 items) and not significantly different compared to controls (median: 2 items). Total NMS of SMA patients did not correlate with disease severity scores. However, the items ‘swallowing difficulties’, ‘falling’ and particularly ‘swelling legs’ were significantly more frequently reported in SMA. Neuropsychiatric symptoms were reported in a frequency comparable to controls and were not significantly increased in SMA. Conclusion: Patient-reported prevalence of NMS in adult SMA was low, which does not argue for a clinically relevant multisystemic disorder in SMAII/III. Importantly, adult SMA patients do not seem to suffer more frequently from symptoms of depression or adaptive disorders compared to controls. Our results yield novel information on previously underreported symptoms and will help to improve the medical guidance of these patients.